Oral hygiene in reducing the incidence of pneumonia associated with mechanical ventilation in pediatric intensive care patients - Martina de Jesús Aguilar Pesántez; Carmen Cecilia Ordoñez Montero; Lorena Elizabeth Padilla Romero; Dolores Amparito Rodríguez Sánchez; Jorge Gayol Samutlón (International Journal of Medical Toxicology and Legal Medicine, 2024)
Introduction: A large number of critically ill pediatric patients who are hospitalized in an intensive care unit (ICU) require mechanical ventilation (MV). MV being the predisposing risk factor that causes Nosocomial Pneumonia (NN). Objective: To analyze the effectiveness of respiratory care practices such as Oral Hygiene in reducing the incidence of Pneumonia associated with Mechanical Ventilation in pediatric Intensive Care patients. Methodology: This research uses a qualitative, descriptive design through a systematic review of documents related to the topic based on the literature search under the Prisma method. Results: Applying the inclusion and exclusion criteria, 616 results were obtained through the Pubmed, Medline, and Web of Science databases. After a complete review of the texts, 20 articles were selected to carry out this review using the Mendely manager. Discussion: the infection is considered acquired in the Intensive Care Unit (ICU) when it is diagnosed after 48 hours of stay; 1 in 4 patients in the ICU acquire infection during their course in the hospital. One of the most feared complications in the PICU are HAIs; these are generally associated with the use of mechanical ventilation, whether invasive or non-invasive. Conclusions: The prevalence of ventilator-associated pneumonia in pediatric intensive care patients demonstrates the importance of this complication in medical care.